Performance of four-rowed Indian mustard (Brassica juncea) mutant under different levels of nitrogen and phosphorus - KUMAR, ANIL; SINGH, BIKRAM; YADAV, Y P; DHANKHAR, O P (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 1997-99 at Bawal on 4-rowed Indian mustard or raya [Brassica juncea (L.) Czernj. & Cosson] mutant to study its yield output at different levels of nitrogen (0,30,60,90 and 120 kg/ha) and phosphorus (0,15,30 and 45 kg/ha). The days taken to 50 % flowering was significantly delayed by 7-8 days at 90 kg and 120 kg N/ha over the control. Light interception (%), leaf-area index, total number of siliquae / plant and number of siliquae on main shoot were significantly maximum at 120 kg N/ha and 37.35 kg P/ha compared with lower doses of both the nutrients. The 1 000-seed weight, oil yield and seed yield responded significantly up to 90 kg N/ha and 24.90 kg P/ha, however, secondary branches increased significantly up to 90 kg N/ha and 37.35 kg P/ha. On an average of 2 years, the increase in the seed yield with the application of phosphorus @ 12.45, 24,90 and 37.35 kg/ha was 16.5, 25.7 and 30.3% over no phosphorus treatment, whereas application of nitrogen @ 30,60,90 and 120 kg/ha increase in the seed yield to 50.8, 86.5, 108.9 and 122.4% respectively over the control. The oil content was significantly decreased with an increase in level of N up to 120 kg /ha, whereas P had no significant effect on oil content under light textured soils of semi-arid climate.